THE RELATIONSHIP BETWEEN THE PHYSICAL CONDITION OF THE HOME ENVIRONMENT AND HISTORY OF DISEASE WITH THE INCIDENCE OF TUBERCULOSIS IN THE WORKING AREA OF THE RANGKASBITUNG HEALTH CENTER IN 2023 - Windarti; Ismarina; Marthia Ikhlasiah (ZILLZELL MEDIA PRIMA, 2024)
This study aims to determine the relationship between the physical condition of the home environment and history of disease with the incidence of tuberculosis or pulmonary tuberculosis in the work area of the Rangkasbitung Health Center in 2023. This study is a descriptive correlation study with cross sectional design, which is research that explores the relationship between the physical condition of the house and the behavior of residents towards the incidence of tuberculosis. The type of data used is primary data, from the results of questionnaires and secondary data obtained from recording and reporting TB patient visit data at the Rangkasbitung Health Center. Data analysis in the study, using univariate analysis with positive TB incidence results (69.2%); Bivariate analysis showed a relationship between home air circulation and the incidence of tuberculosis (P<0.028), occupancy density (P<0.011), lighting (P<0.015), humidity (P<0.020), education (P<0.002), employment (P<0.006), and smoking (P<0.009); and humidity factor being the dominant factor with the largest OR (OR=28.579). The results of the cross-sectional test in the study, showed a significant relationship between the physical condition of the home environment and the history of disease with the incidence of tuberculosis in the work area of the Rangkasbitung Health Center. Suggestions in this study are the need for education related to environmental factors and behaviors that cause tuberculosis, such as counseling about healthy homes with qualified ventilation, good lighting, good humidity, occupancy in an adequate place, and reducing cigarette use habits. Other factors that need to be improved, in order to support the reduction in TB prevalence rates, namely education and employment factors. Patients with pulmonary tuberculosis must also be given understanding, related must always be tried to be in a place that has adequate air ventilation and good humidity, in order to reduce the risk of the severity of TB disease which can lead to death or the duration of the treatment process.